PENGARUH SIKLUS KONVERSI KAS TERHADAP PROFITABILITAS PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA TAHUN 2008-2011 - Iva Indarnika Cahaya Martha; Indira Januarti (Diponegoro Journal of Accounting, 2013)
This study aims to determine the effect of cash conversion cycle on profitability. Cash conversion cycle consists of three components: number of days inventory, number of days accounts receivable and number of days accounts payable. Profitability is measured by gross operating income. Population of this research are manufacturing companies which listed in Indonesian Stock Exchange (BEI). The sample are manufacturing companies which listing in Indonesian Stock Exchange (BEI) during 2008-2011 and comply sample criteria. Total sample are 104 companies. The result of this research show that cash conversion cycle had significant and negatif effect to profitability.